Camp sites : sex, politics, and academic style in postwar America - Trask, Michael, 1967- (Post 45., 2013)
Reading across the disciplines of the mid-century university, this book argues that the political shift in postwar America from consensus liberalism to New Left radicalism entailed as many continuities as ruptures. Both Cold War liberals and radicals understood the university as a privileged site for ""doing politics, "" and both exiled homosexuality from the political ideals each group favored. Liberals, who advanced a politics of style over substance, saw gay people as unable to separate the two, as incapable of maintaining the opportunistic suspension of disbelief on which a tough-mind.